Primer uporabe najpreprostejšega statističnega testa - Vidmar, Gaj (Rehabilitacija (Ljubljana), 2008)
Background: The Institute for Rehabilitation, Republic of Slovenia (IRSR), has recently conducted several analyses of changes in demandingness of inpatient care since 2000, which include the study of frequency of complications and concomitant diagnoses. Methods: The study was based on medical documentation - patient records. For 2001, 2004 and 2007, we randomly selected 20 records from each of the six studied wards of the IRSR. The estimated number of diagnoses and complications per patient was compared between the years using the asymptotic test for difference between two Poisson ratios. Results: The number of diagnoses per patient was statistically significantly larger in 2004 as well as in 2007 compared to 2001. The increase from 2004 to 2007 was not statistically significant. The recorded number of complications per patient was also larger in 2004 and 2007 than in 2001, but the difference is not statistically significant. Conclusions: The application of the "simplest statistical test" gave us a useful "feel of the data", showing increased demandingness of inpatient rehabilitation.
Keywords: rehabilitacija; vocational rehabilitation; medicinska dokumentacija